Methanococcus jannaschii Flap Endonuclease: Expression, Purification, and Substrate Requirements - Rao, H. G. V. (American Society for Microbiology, 1998)
The flap endonuclease (FEN) of the hyperthermophilic archaeon Methanococcus jannaschii was expressed in Escherichia coli and purified to homogeneity. FEN retained activity after preincubation at 95°C for 15 min. A pseudo-Y-shaped substrate was formed by hybridization of two partially complementary oligonucleotides. FEN cleaved the strand with the free 5′ end adjacent to the single-strand–duplex junction. Deletion of the free 3′ end prevented cleavage. Hybridization of a complementary oligonucleotide to the free 3′ end moved the cleavage site by 1 to 2 nucleotides. Hybridization of excess complementary oligonucleotide to the free 5′ end failed to block cleavage, although this substrate was refractory to cleavage by the 5′-3′ exonuclease activity of Taq DNA polymerase. For verification, the free 5′ end was replaced by an internally labeled hairpin structure. This structure was a substrate for FEN but became a substrate for Taq DNA polymerase only after exonucleolytic cleavage had destabilized the hairpin. A circular duplex substrate with a 5′ single-stranded branch was formed by primer extension of a partially complementary oligonucleotide on virion φX174. This denaturation-resistant substrate was used to examine the effects of temperature and solution properties, such as pH, salt, and divalent ion concentration on the turnover number of the enzyme.